Accurate determination of reference wind speed and reference static pressure in wind tunnel tests. Issue 3 (February 2020) - He, YC; Cheung, JCK; Li, QS; Fu, JY
The reference wind speed and reference static pressure are two key parameters for determining the testing results of wind tunnel experiments. Traditionally, the values of these parameters can be determined using direct measurement methods. However, such methods may suffer from less accuracy and inconvenience of operations. This article documents an indirect measurement method which, compared to the traditional methods, has the merits of higher accuracy and greater operational convenience. Examples are presented to demonstrate the main procedures of the method and typical findings by using the method in a boundary layer wind tunnel.